Synthesis of Eco-Friendly Bioplastic from Banana Hump Starch and Sugarcane Bagasse Cellulose Filler with Fish Scale Chitosan - Agustina, Ayu Safitri; Jumrah, Elfira; Abubakar, Andi Nur Fitriani (Hasanuddin University, 2023)
This study aims to make environmentally friendly bioplastics. This is because the use of plastic creates a plastic waste problem which is very difficult to handle. After all, it is difficult to decompose. Excessive use of plastic will be bad for the safety of the earth in the future. One of the innovations to be developed is the synthesis of environmentally friendly bioplastics. The basic ingredients for making bioplastics come from starch, cellulose, and chitosan. The process of making bioplastics uses several formulations including A0 (control), A1, A2 and A3. The research results showed that the biodegradability test was good for the A3 formula and the water absorption test was 3.77% and water resistance was 96.2%.